Measurement and correlation of wedged hepatic, intrahepatic, intrasplenic and intravariceal pressures in patients with cirrhosis of liver and non-cirrhotic portal fibrosis. Issue 3 (March 1987) - Sarin, S K; Sethi, K K; Nanda, R
Abstract : In order to examine the relationship of various haemodynamic parameters in two different liver diseases, 10 patients with cirrhosis of liver and 14 patients with non-cirrhotic portal fibrosis were studied. In cirrhotics, mean (+/- SD) wedged hepatic (25.8 +/- 6.4 mmHg), intrahepatic (24.5 +/- 6.2 mmHg) and intrasplenic (25.0 +/- 5.6 mmHg) pressures correlated significantly (p less than 0.001) with intravariceal (25.2 +/- 6.7) pressure measurements. In patients with NCPF, mean (+/- SD) wedged hepatic (9.1 +/- 3.7 mmHg) and intraphepatic (15.4 +/- 5.8 mmHg) pressures were significantly (p less than 0.01) lower than the intrasplenic (24.5 +/- 4.2 mmHg) and intravariceal (23.96 +/- 5.6 mmHg) pressures. Two independent pressure gradients, one between intrasplenic and intrahepatic pressure (8.9 +/- 6.5 mmHg) and another between intrahepatic and wedged hepatic venous pressure (6.2 +/- 5.6 mmHg) were seen in non-cirrhotic portal fibrosis patients, indicating the likelihood of both pre- and perisinusoidal resistance to flow of portal venous blood in these patients. A highly significant (p less than 0.001) correlation between intravariceal and intrasplenic pressures was found in patients with cirrhosis of liver (r = 0.93), as well as in patients with non-cirrhotic portal fibrosis (r = 0.85). No correlation was found between the size of oesophageal varices and wedged hepatic and intrahepatic pressures. Patients with grade 4 varices had significantly higher intravariceal (p less than 0.01) and intrasplenic (p less than 0.05) pressure than patients with grade 2 varices. It can be concluded that intravariceal pressure is representative of portal pressure in patients with cirrhosis of liver as well as in non-cirrhotic portal fibrosis patients and it can be recommended as the single haemodynamic investigation in patients with portal hypertension and oesophageal varices.